Underestimation of spirometry if recommended testing guidance is not followed. (12th February 2018) - Sumner, J; Robinson, E; Bradshaw, L; Lewis, L; Warren, N; Young, C; Fishwick, D
Abstract: Background: Lung function measured at work is used to make important employment decisions. Improving its quality will reduce misclassification and allow more accurate longitudinal interpretation over time. Aims: To assess the amount by which lung function (forced expiratory volume in 1 second [FEV1 ] and forced vital capacity [FVC]) values will be underestimated if recommended spirometry testing guidance is not followed. Methods: Lung function was measured in a population of workers. Knowledge of the final reproducible FEV1 and FVC for each worker allowed estimation of the underestimates that would have occurred if less forced manoeuvres than recommended had been performed. Results: A total of 667 workers (661 males, mean age 43 years, range 18–66) participated. Among them, 560 (84%) achieved reproducible results for both FEV1 and FVC; 470 (84%) of these did so after three technically acceptable forced expiratory manoeuvres, a cumulative total of 533 after four, 548 after five, 557 after six, 559 after seven and 560 after eight blows. If only one (or first two) technically acceptable blow(s) had been performed, mean underestimates were calculated for FEV1 of 115.1 ml (35.4 ml) and for FVC of 143.4 ml (42.3 ml). Conclusions: In this study, reproducible spirometry was achievable in most workers. Not adhering to standards underestimates lung function by clinically significant amounts.